Attitudes towards doping in Spanish competitive female cyclists vs. triathletes - Morente-Sanchez, J.; Leruite, M.; Mateo-March, M.; Zabala, M. (Journal of Science and Cycling, 2013)
The aim of the present study was to know and compare the attitudes towards doping in Spanish competitive female cyclists and triathletes. All the female cyclists and triathletes who competed (U23 and elite) under license in Spain in 2012 (n = 206; 29.62±8.70 years) in the highest national competitions level comprised the sample. The total sample was divided into two: cyclists (n = 80; 28.86±9.64 years), and triathletes (n = 126; 30.10±8.06 years). Descriptive design was carried out using a validated questionnaire (Performance Enhancement Attitude Scale: PEAS). Complementary, four top-level athletes of each group were interviewed. Regarding results from PEAS, for the whole sample, overall score (17-102) was 34.02±12.74. Regarding different groups, data were: cyclists: 36.63±14.27; and triathletes: 32.37±11.41 (p=0.032). Regarding semi-structured interviews (n = 8). The most mentioned word associated with doping was "cheating" (% n: 62.5). As responsible agents of doping was the word "coach/manager" (% n: 75.0) and the main reason for the initiation in doping was "sport achievement" and "Contract/Money" (% n: 75.0). This study shows that Spanish competitive female cyclists and triathletes, in general, are not tolerant in relation to doping. Nevertheless, competitive female cyclists are significantly more permissive towards the use of banned substances than female triathletes. Results from semi-structured interviews have shown interesting data in specific open-ended questions. The current findings may contribute to the development of anti-doping prevention programmes and interventions in an appropriate and effective manner, which could be the key to better fight the battle against doping in sport.